Slope stability analysis by integration of seismic refraction method and geotechnical soil testing: Case study of landslide in Bulobulo Village, Barru Regency, Indonesia - Sam, Dwi Nurfajriana; Massinai, Muhammad Altin; Pramatadie, Andi Muhamad (Journal of Degraded and Mining Lands Management, 2025)
This research investigated slope stability issues in Bulobulo Village, Barru Regency in Indonesia, which is known to experience very high landslide occurrences, particularly in steep slopes with seasonally altered overburden rocks through refraction seismic method and geotechnical analysis. This study conducted mechanical and physical soil tests in the laboratory, and the geophysics study investigated subsurface configuration. The set of data collected also reflected some seismic velocity anomalies, which are signs of variations in the arrangement of the substructure. A geotechnical investigation of the slope showed low cohesiveness and high water content, which were detrimental to stability. The factor of safety (FoS) calculated using the limit equilibrium technique established some slopes as being in a critical state and, hence, at risk of landslides. Such integration of methods allows one to make data-driven proposals for landslide prevention and provides a comprehensive comprehension of slope performance.